Recurrent And Delayed Angio-Edema Due To Angiotensin Enzyme Inhibitor - Balasubramaniam P; Ganesan S; Bhat J; Ugoji U U (Wolters Kluwer Medknow Publications, 2003)
Angiotensin converting enzyme inhibitors (ACEI) are now well established and commonly used drugs in the treatment of hypertension and congestive cardiac failure. Recurrent and delayed angio-edema is an uncommon but potentially serious adverse effect of ACEI therapy especially because it often goes unrecognized due to lack of correlation between the long term medications the patients is on and the angio-edema. Our 82 year old patient with recurrent delayed angio-edema was diagnosed 5 years after ACE inhibitor was started. Prompt withdrawal of the drug resulted in complete resolution of the symptoms.